A comparison of blood flow restriction devices to assess limb occlusion pressure in supine and standing positions - Bommasamudram, Tulasiram; Nayak, Kirtana Raghurama; Clarkson, Matthew J.; Kadavigere, Rajagopal; Russell, Aaron P.; Warmington, Stuart A. (Frontiers in Sports and Active Living, 2025)
ObjectiveThe objective of this study was to compare five commercially available blood flow restriction (BFR) devices in determining limb occlusion pressure (LOP), plus two algorithm approaches for determining LOP, in both supine and standing positions.MethodsTwenty-one recreationally active males were assessed for LOP using five BFR devices: Zimmer (surgical-grade tourniquet; reference standard), AirBands, blood pressure cuff with pulse oximeter (BPPO), Smart Cuffs, and Suji. Two additional algorithms based on resting anthropometric/physiological data were also assessed. LOP was measured in both supine and standing positions, with two measurements per posture separated by a five-minute interval. In addition to LOP, participants rated their level of discomfort during each measurement.ResultsWhen compared to the Zimmer device, BPPO (r = 0.636, p = 0.002) and Smart Cuffs (r = 0.758, p < 0.001) demonstrated the closest association in the supine and standing positions, respectively. AirBands exhibited the greatest deviation from Zimmer in both positions but were consistently rated as more comfortable (p > 0.05), even at higher pressures.ConclusionNone of the devices showed consistent LOP measurements across both postures, indicating significant variability depending on device type and body position. These findings underscore the need for posture-specific calibration when using BFR devices and caution against assuming device interchangeability.